Relasi Nietzsche dengan Paulus - Supeno Lembang (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2024)
Nietzsche’s relation with Christianity, on the the surface, easily defined as antipodal, full of animosity. It is not a simple task to specify which Christianity that can represent a stable concept of Christianity. Numerous branches as well as different school of thoughts in the body of Christianity. Nietzsche had his own view on certain Christianity (coloured by his Lutheran Protestant), he was not seldom launched attack after attack to Christianity and blame it as caused of Nihilism in Europe. Christianity according to his view has become one of the obstacles that hindered the arrival of the Overman, therefore he anointed himself to wage war with the aim to dig deep the foundation of Christianity. He did not merely assault Christianity and belief in God as some concepts that is no longer hold, but he wished to make changes and transvalue all the values which had deeply rooted in the soul of Europe. In order to pull down, to root out, change and inspire Europe, he wrote a seminal book called “Antichrist.” Nietzsche in his war strategy, he always picked a real person as Socrates, Richard Wagner, or even Schopenhauer. For Christianity, he picked Paul and Paulinism which he regarded as promoting the concept of Cross, Resurrection and promise of Hinterwelt which according to him is a great move as well as cunning. He tried to uproot Christainity with his method, which later on he called it as Genealogy. In doing so, he discovered that Paul was a true revaluator, who reevaluated the master morality into slave morality. Nietzsche has his own notion of an ideal man, who has the spirit of Dionysos, in short, he wanted to transvalue the slave morality back to master morality. In suggesting this option to Europe, a better choice, Spirit of Dionysos, he then conducted transvaluation. In that regard, Nietzsche did a similar and kinship “Hegelian Dialectic” with Paul. Therefore, Nietzsche relation with Paul is no longer can be categorized as merely antipodal, since he showed some kind of disguised adoration, an ambiguity.